Inhibition of Female and Male Human Detrusor Smooth Muscle Contraction by the Rac Inhibitors EHT1864 and NSC23766 - Li, Bingsheng; Yu, Qingfeng; Wang, Ruixiao; Gratzke, Christian; Wang, Xiaolong; Spek, Annabel; Herlemann, Annika; Tamalunas, Alexander; Strittmatter, Frank; Waidelich, Raphaela; Stief, Christian G.; Hennenberg, Martin (Frontiers in Pharmacology, 2020)
Introduction: Lower urinary tract symptoms (LUTS) due to overactive bladder (OAB) are caused by spontaneous detrusor contractions. Medical treatment with muscarinic receptor antagonists or β3-adrenoceptor agonists aims to inhibit detrusor contractions, but overall results are unsatisfactory. Consequently, improved understanding of bladder smooth muscle contraction and identification of novel compounds for its inhibition are needed to develop alternative options. A role of the GTPase Rac1 for smooth muscle contraction has been reported from the prostate, but is unknown in the human detrusor. Here, we examined effects of the Rac inhibitors NSC23766, which may also antagonize muscarinic receptors, and EHT1864 on contraction of human detrusor tissues. Methods: Female and male human detrusor tissues were obtained from radical cystectomy. Effects of NSC23766 (100 µM) and EHT1864 (100 µM) on detrusor contractions were studied in an organ bath. Results: Electric field stimulation induced frequence-dependent contractions of detrusor tissues, which were inhibited by NSC23766 and EHT1864. Carbachol induced concentration-dependent contractions. Concentration response curves for carbachol were shifted to the right by NSC23766, reflected by increased EC50 values, but unchanged Emax values. EHT1864 reduced carbachol-induced contractions, resulting in reduced Emax values for carbachol. The thromboxane analog U46619 induced concentration-dependent contractions, which remained unchanged by NSC23766, but were reduced by EHT1864. Conclusions: NSC23766 and EHT1864 inhibit female and male human detrusor contractions. NSC23766, but not EHT1864 competitively antagonizes muscarinic receptors. In addition to neurogenic and cholinergic contractions, EHT1864 inhibits thromboxane A2-induced detrusor contractions. The latter may be promising, as the origin of spontaneous detrusor contractions in OAB is non-cholinergic. In vivo, both compounds may improve OAB-related LUTS.